2014
DOI: 10.1016/j.jinsphys.2014.05.020
|View full text |Cite
|
Sign up to set email alerts
|

Ambient temperature and dietary supplementation interact to shape mosquito vector competence for malaria

Abstract: The extent to which environmental factors influence the ability of Anopheles mosquitoes to transmit malaria parasites remains poorly explored. Environmental variation, such as change in ambient temperature, will not necessarily influence the rates of host and parasite processes equivalently, potentially resulting in complex effects on infection outcomes. As proof of principle, we used Anopheles stephensi and the rodent malaria parasite, Plasmodium yoelii, to examine the effects of a range of constant temperatu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(44 citation statements)
references
References 59 publications
(73 reference statements)
3
40
1
Order By: Relevance
“…[52][53][54][55][56][57][58][59][60][61] Temperature has clear impacts on vector-borne diseases through effects on the insect vectors; mosquitoes are ectotherms and their internal body temperature varies considerably with variation in ambient temperature. Mosquito physiology (e.g., immunity), [62][63][64] life history (e.g., development, survival, reproduction, biting rates), 40,[65][66][67] and arbovirus fitness (e.g., vector competence and extrinsic incubation periods) [68][69][70][71][72] are all directly affected by temperature variation. Future climate change will likely alter the climate conditions that mosquito vectors experience, but it remains unclear how mosquito vectors will respond.…”
Section: Arbovirus Transmission In a Changing Worldmentioning
confidence: 99%
“…[52][53][54][55][56][57][58][59][60][61] Temperature has clear impacts on vector-borne diseases through effects on the insect vectors; mosquitoes are ectotherms and their internal body temperature varies considerably with variation in ambient temperature. Mosquito physiology (e.g., immunity), [62][63][64] life history (e.g., development, survival, reproduction, biting rates), 40,[65][66][67] and arbovirus fitness (e.g., vector competence and extrinsic incubation periods) [68][69][70][71][72] are all directly affected by temperature variation. Future climate change will likely alter the climate conditions that mosquito vectors experience, but it remains unclear how mosquito vectors will respond.…”
Section: Arbovirus Transmission In a Changing Worldmentioning
confidence: 99%
“…Dependence on the external environment for body temperature control has significant impacts on insect physiological functioning (Chown & Nicolson, 2004) and, subsequently, life‐history traits (Ciota, Matacchiero, Kilpatrick, & Kramer, 2014; Clissold & Simpson, 2015; Lachenicht, Clusella‐Trullas, Boardman, Le Roux, & Terblanche, 2010). Temperature effects may be particularly important when considering the immune system, as responses to temperature variation can have direct consequences for both pathogen infection and host survival (Alto & Bettinardi, 2013; Murdock, Blanford, Luckhart, & Thomas, 2014; Pamminger, Steier, & Tragust, 2016; Pounds et al., 2006; Richards, Anderson, Lord, & Tabachnick, 2012; Wolinska & King, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…This could impact the vectorial capacity of insect vectors of malaria and other pathogens. In [95], it was demonstrated that ambient temperature influences the expression of immune genes that can regulate the intensity of Plasmodium yoelii infection in An. stephensi mosquitoes.…”
Section: The Role Of Climate In Insect Vector-pathogen Interactionsmentioning
confidence: 99%